Evaluating the Impact of Comprehensive Smoking Cessation Programs on Adolescents Smoking Behavior and Nicotine Dependence - Sari, Winda; Makmur, Nandar; Abdullah, Hasbi (ScieClouds Publishing, 2024)
Adolescent smoking remains a significant public health issue globally, with millions of young individuals continuing to smoke despite widespread anti-smoking campaigns. This study aimed to evaluate the effectiveness of smoking cessation programs for adolescents, focusing on reducing smoking frequency, nicotine dependence, and improving quit rates. A total of 200 adolescents participated, with 100 in the experimental group undergoing a comprehensive smoking cessation program combining behavioral therapy and pharmacotherapy, while the control group received standard health education. Results showed that the experimental group experienced a significant reduction in smoking frequency and nicotine dependence, as evidenced by lower scores on the Fagerström Test for Nicotine Dependence (FTND) and self-reported smoking behavior. The quit rate in the experimental group was 55%, compared to 30% in the control group. Furthermore, the program’s integration of mobile health tools and school-based support structures was particularly effective in engaging participants. The findings highlight the importance of multifaceted interventions tailored to the specific needs of adolescents, emphasizing behavioral, pharmacological, and technological support. This study provides valuable insights into the potential of comprehensive, youth-centered smoking cessation programs and advocates for further research into their long-term effectiveness and scalability